Sincere action or sweet talk: how do firms respond to retail investors' green appeals? - He, Ling (Journal of business ethics, 2025)
With the rise in global awareness of sustainable transition, investor groups have become continuously engaged in pressuring firms to improve their environmental performance. However, there is limited knowledge about whether firms respond to these pressures through substantive actions or symbolic gestures. Based on the ethical decision-making framework, our study examines the relationship between retail investors' green appeals and corporate greenwashing. Our results show that retail investors' green appeals result in significant increases in corporate greenwashing, suggesting that firms are more inclined to adopt symbolic gestures in response to these investor aspirations. Meanwhile, we find that the information asymmetry and the short-term investment horizon of retail investors are two primary reasons for firms’ adoption of greenwashing in response to retail investors' green appeals. This positive relationship is more pronounced in firms with opportunistic executives, financial constraints, weak environmental ethics, and without political connections. The consequences of greenwashing reveal that while corporate greenwashing behavior may receive positive market reactions in the short term, in the long term, regulators will recognize this behavior resulting in penalties for the firm.